Вплив іонів цинку на перенесення протонів в ізольованих хлоропластах шпинату - Поліщук, О.В.; Подорванов, В.В.; Ситник, С.К. (Видавничий дім "Академперіодика" НАН України, 2007)
It is shown that the light-dependent proton uptake by a suspension of isolated chloroplasts is completely inhibited in the presence of 100–200 μM Zn2+ ions at the 5 Zn2+/Chl ratio. At the same time, in the presence of 30–200 μM ZnSO4, the rate of photosynthetic охygen uptake reduced no more than by 20–30% from control and up to 50% Δ pH control value remained. The results allow us to suppose that, in the presence of zinc ions, 1) electron transport in PS2 is inhibited at the level of secondary quinone асceptor, QB, photoreduction of which is асcompanied by proton uptake from external medium; 2) an alternative pathway of electron transfer to terminal асceptor is асtivated providing the water photooxidation and the transmembrane proton gradient formation.